Morphological and molecular characterization of Ustilaginoidea virens isolates causing false smut of rice in India - and DEEBA KAMIL, MATHEW S. BAITE*, R.K. SHARMA, T. PRAMEELA DEVI, PRATIBHA SHARMA (Indian Phytopathology, 2014)
Different isolates of Ustilaginoidea virens showed variation in the size, colour and shape of the conidia, length of spines and width of the hyphae. The conidia were globose, irregularly round to elliptical and warty on the surface with diameters ranging from 4.20 to 6.54 µm. The scanning electron microscopy revealed that the conidial wall was echinulated and ornamented with prominent spines. The spines were pointed at the apex or irregularly curved and ranged from 359.9–994.5 nm long. Based on colony characters isolates of U. virens were grouped into three groups. The maximum colony diameter was observed in isolate UV3 (40 mm) while minimum was in UV7 (25 mm). The width of the hyphae in different isolates varied from 1.26-2.81 µm. The maximum width of the hypha was 2.81 µm in UV4 isolate and minimum in UV3 (1.26 µm). The genetic diversity of the eight isolates of U. virens, by random amplified polymorphic DNA (RAPD) marker using nine primers, revealed a considerable level of genetic variation. The dendrogram showed two main clusters; cluster I comprised of five isolates (UV1, UV5, UV8, UV6 and UV7), while Cluster II consisted of three isolates (UV2, UV3 and UV4).